2015
DOI: 10.1007/s10552-015-0683-4
|View full text |Cite|
|
Sign up to set email alerts
|

Patterns and correlates of accelerometer-assessed physical activity and sedentary time among colon cancer survivors

Abstract: The low level of MVPA and high volume of sedentary time demonstrated by these objective data highlight the need for intervention in colon cancer survivors. The correlates and accumulation patterns described by this study may better inform interventions and translational research designed to increase physical activity and reduce sedentary behavior in colon cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 29 publications
7
62
1
Order By: Relevance
“…Likewise, other studies Lynch et al, 2016;Peddle et al, 2008) found that being employed, having less occupational experience, and higher economic status, respectively, were related to complying with the recommendations of moderate and vigorous physical activity by the institutions of reference. In addition, a lower annual income has been associated with showing less interest in starting a physical activity program for patients with colorectal cancer (McGowan, Speed-Andrews, .…”
Section: Sociodemographic Factorsmentioning
confidence: 78%
See 4 more Smart Citations
“…Likewise, other studies Lynch et al, 2016;Peddle et al, 2008) found that being employed, having less occupational experience, and higher economic status, respectively, were related to complying with the recommendations of moderate and vigorous physical activity by the institutions of reference. In addition, a lower annual income has been associated with showing less interest in starting a physical activity program for patients with colorectal cancer (McGowan, Speed-Andrews, .…”
Section: Sociodemographic Factorsmentioning
confidence: 78%
“…On another hand, van Putten et al (2016) found that the intensity of physical activity in colorectal cancer patients was relatively stable during and after treatment but men performed more moderate-vigorous physical activity than women. In this sense, another study revealed that women performed more light physical activity and men spent more time sitting (Lynch et al, 2016).…”
Section: Sociodemographic Factorsmentioning
confidence: 94%
See 3 more Smart Citations